Effects of coordination training on the technical development in 10-/13-year-old football players - Kösal, M.; Gül, G. K.; Doganay, M.; Álvarez-García, C. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The aim of this study was to determine the effects of coordination training carried out by 10- and 13-year-old male football players on the performance of dribbling, passing, shooting, ball bouncing and wall-volley skills. METHODS: A total of 45 male football players were divided into three 15 participants groups. The experimental group performed 30 min coordination training three days a week for ten weeks while the control group one continued their routine training and control group two performed unstructured football training. Measurements included Mor and Christian, Yeagley and Johnson football skill tests. Pre- and post-test measurements were compared by an ANOVA 2×3. A significant level of P<0.05 was established. RESULTS: All the skills, dribbling (P<0.001), passing (P<0.001), shooting (P<0.001), ball bouncing (P=0.047) and wall-volley (P<0.001), improved after ten weeks in the experimental group, while only passing (P=0.006), shooting (P=0.007) and wall-volley (P<0.001) improved in the control group one and none of the skills improved in the control group two (P>0.05). The improvement was significant in the experimental group in comparison with the control groups (P<0.001). CONCLUSIONS: The implementation of coordination exercises in combination with structured football training has been shown to be effective in improving general football ability among 10-13 male players.